Tren dan Isu Ekonomi Islam: Sistemik Literatur Review - Iswandi, Andi (Prodi Ekonomi Syariah, Fakultas Syariah, Institut PTIQ Jakarta, 2024)
This study explores the trend of Islamic economics research through a systematic review of the literature to understand the contributions and developments in this field in the context of sustainable and inclusive development. The trend of Islamic economics research has shown a significant increase in recent years, especially considering the dynamics of the ever-evolving global economy. Various studies have shown that the Islamic economic system has great potential in supporting sustainable and inclusive development in various countries, especially Muslim-majority countries. This study uses a qualitative approach with a literature review method to collect, identify, and analyze various findings from previous studies. The data used comes from scientific articles published in reputable journals between 2020 and 2024. Bibliometric analysis using VOSviewer shows the existence of three main clusters in Islamic economics research covering topics such as Islamic finance, Islamic banking, and design methodology in Islamic finance. This study found that the number of articles and citations related to Islamic economics indexed in Scopus fluctuated with a peak of articles in 2018 and 2021 and a peak of citations in 2018. Geographically, this study shows that countries such as the United States, Malaysia, the United Kingdom, and Indonesia are major contributors to Islamic economics research. The conclusion of this study shows that the Islamic economic system has great potential to support sustainable and inclusive development, but further research is needed to overcome challenges and expand its application in the context of a modern economy.